The Influence of Drying Method on Volatile Composition and Sensory Profile of Boletus edulis - Joanna Nöfer; Krzysztof Lech; Adam Figiel; Antoni Szumny; Ángel A. Carbonell-Barrachina (Journal of Food Quality)
The objective of this study was to evaluate the influence of different drying methods on aroma and sensory profile of Boletus edulis (cepe). The drying methods tested were convective drying (CD), freeze-drying (FD), vacuum microwave drying (VMD), and a combination of convective predrying and vacuum microwave finish-drying (CPD-VMFD). Fresh and dried cepe volatiles, analyzed by SPME and GC-MS, showed the presence of 53 volatile compounds, most of them present in all dried samples but with quantitative variation. The major volatile compounds in fresh and dried cepe were 1-octen-3-ol (3405 µg 100 g−1·db), 3-octanone (429 µg 100 g−1·db), and hexanal (355 µg 100 g−1·db). The results showed that drying of cepe mushrooms caused major losses of aroma compounds; however, the highest content of volatile compounds and the highest intensity of most of the key positive sensory attributes were found in samples after (i) CD at 80°C (3763 µg 100 g−1·db), (ii) CD at 70°C (3478 µg 100 g−1·db), and (iii) CPD at 60°C and VMFD at 480/240 W (2897 µg 100 g−1·db).